Efficacy and safety of stratified versus routine prophylaxis in living kidney transplantation from HBsAg+ donors to HBsAg− recipients: protocol for a multicentre, prospective, observational study. Issue 12 (30th December 2021) - Wang, Xianding; Yin, Saifu; Song, Turun; Huang, Zhongli; Fan, Yu; Liu, Hongtao; Shang, Wenjun; Zhou, Honglan; Li, Xiaohong; Lin, Tao
Abstract : Introduction: It remains unclear whether kidney transplantation (KT) from hepatitis B surface antigen (HBsAg) +donors to HBsAg− recipients (D(HBsAg+)/R(HBsAg−)) provides comparable transplant outcomes without hepatitis B virus (HBV) transmission compared with D(HBsAg−)/R(HBsAg−) KT. Moreover, no consensus has been reached for standardised prophylaxis regimens to prevent HBV transmission after D(HBsAg+)/R(HBsAg−) KT. We developed stratified prophylaxis regimens, including pretransplant antiviral treatment of donors, and pretransplant hepatitis B vaccination and post-transplant antiviral treatment of recipients, based on donors' and recipients' HBV serological characteristics. However, the safety and efficacy of stratified prophylaxis regimens remains unknown. Methods and analysis: We are conducting a prospective, multicentre, observational study. Between September 2020 and December 2023, 100 cases of (D(HBsAg+)/R (HBsAg−)) KT will be recruited from four university-affiliated hospitals with a follow-up at least 2 years. They will naturally receive stratified prophylaxis regimens or routine prophylaxis based on clinical experience to compare the efficacy and safety of these two regimens in (D(HBsAg+)/R(HBsAg−)) KT. The primary outcome will be post-transplant HBV infection to evaluate safety, defined as post-transplant HBsAg−→+or HBV DNA−→+. The composite endpoint of prevention failure will be also an endpoint of safety (any one of HBsAg−→+, HBV DNA−→+, HB e antigen−→+, HB e antibody−→+ and HB c antibody−→+). The efficacy will be evaluated by transplant outcomes, including death-censored graft survival, patient survival, acute rejection, delayed graft function and kidney graft function. Ethics and dissemination: This study will be registered as a clinical audit at each participating hospital and has obtained approval from the Ethics Committee of West China Hospital (reference: 2020-683, 8 September 2020). Trial registration number: NCT04562051 .